A pipeline to link meteorological information and TGFs detected by AGILE. Issue 2 (11th February 2017) - Ursi, A.; Sanò, P.; Casella, D.; Marisaldi, M.; Dietrich, S.; Tavani, M.
Abstract: Terrestrial gamma ray flashes (TGFs) are brief (approximately hundreds of microseconds) intense gamma ray emissions coming from Earth's atmosphere (∼15 km above sea level), correlated with thunderstorms and atmospheric electric activity. Since their unexpected discovery in the early 1990s by the Burst And Transient Source Experiment/Compton Gamma Ray Observatory, TGFs have been further investigated by several satellites devoted to high‐energy astrophysics. The Astrorivelatore Gamma ad Immagini LEggero (AGILE) mission turned out to be particularly suitable to detect these events, due to a very wide energy range (up to 100 MeV), an optimized triggering system, and a unique low‐inclination near‐equatorial orbit (2.5°). We describe a detection system, developed for the AGILE satellite, whose aim is to provide real‐time meteorological information on each detected TGF. We take advantage of data acquired by geostationary satellites to promptly identify the associated storm and follow its evolution in space and time, in order to study its previous onset and development. Data from Low‐Earth Orbit meteorological satellites, such as the Global Precipitation Mission, as well as ground measurements from lightning detection networks, can be integrated in the pipeline. This system allows us a prompt characterization of the ground meteorological conditions at TGF time which will provide instrument‐independent trigger validation, fill in a database for subsequent statistical analysis, and eventually, on a longer term perspective, serve as a real‐time alert service open to the community. Key Points: The AGILE satellite has a TGF database linked to meteorological information Geostationary satellite data are processed to extract information on TGF‐producing thunderstorms This pipeline allows for further meteorological studies about the physics of TGFs